Il Museo Glass Beacon nei Mercati di Traiano – Museo dei Fori Imperiali: sperimentazione di storytelling in un museo di architettura antica - Maria Caterina Schettini (mediaGEO soc. coop., 2017)
"The Museo Glass Beacon: the Museum of the Future” is an experimental project realized in the Museum of Imperial Fora in collaboration with ETT S.p.A., a company with experience in applying new technologies in the cultural industry.